2008
DOI: 10.1038/nn2077
|View full text |Cite
|
Sign up to set email alerts
|

Modulators of decision making

Abstract: Human and animal decisions are modulated by a variety of environmental and intrinsic contexts. Here I consider computational factors that can affect decision making and review anatomical structures and neurochemical systems that are related to contextual modulation of decision making. Expectation of a high reward can motivate a subject to go for an action despite a large cost, a decision that is influenced by dopamine in the anterior cingulate cortex. Uncertainty of action outcomes can promote risk taking and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
396
0
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 554 publications
(417 citation statements)
references
References 85 publications
13
396
0
8
Order By: Relevance
“…We make more complex decisions in the real world where both positive and negative outcomes are possible, and have to pay attention to relative differences in the magnitude of gains and losses. A computational model has suggested that tonic D 2 receptor stimulation in the striatum inhibits response to avoid negative outcomes (Frank et al, 2007), and other neurotransmitters such as serotonin and noradrenaline are thought to be involved in the complex decision-making process (Trepel et al, 2005;Frank et al, 2007;Cools et al, 2008;Doya, 2008). Using behavioral tasks with negative outcomes, future studies to investigate involvements of other neurotransmissions as well as other areas that are related to punishment or negative emotions such as the orbitofrontal cortex, insula and amygdala (Trepel et al, 2005;Pessiglione et al, 2006;Voon et al, 2010) are recommended.…”
Section: Discussionmentioning
confidence: 99%
“…We make more complex decisions in the real world where both positive and negative outcomes are possible, and have to pay attention to relative differences in the magnitude of gains and losses. A computational model has suggested that tonic D 2 receptor stimulation in the striatum inhibits response to avoid negative outcomes (Frank et al, 2007), and other neurotransmitters such as serotonin and noradrenaline are thought to be involved in the complex decision-making process (Trepel et al, 2005;Frank et al, 2007;Cools et al, 2008;Doya, 2008). Using behavioral tasks with negative outcomes, future studies to investigate involvements of other neurotransmissions as well as other areas that are related to punishment or negative emotions such as the orbitofrontal cortex, insula and amygdala (Trepel et al, 2005;Pessiglione et al, 2006;Voon et al, 2010) are recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Pessiglione et al (2006) showed that the administration of DA drugs affects decision-making over gains but not over losses at both the behavioural and the neural levels. Thus, the pharmacological evidence suggests the probable involvement of additional neurotransmitters in the loss domain, especially serotonin, which may have a role in predicting short-and long-term rewards in the ventral and dorsal striatum (Tanaka et al 2007;Doya 2008). Further imaging genetics studies using same behavioural tasks would greatly enhance our understanding about the role of neurotransmitters and brain regions in modulating decision-making under risk over gains and losses.…”
Section: Discussionmentioning
confidence: 99%
“…Both dopamine and serotonin interact with other neuromodulators to influence choice (Doya, 2008). However, I will not consider proposals that phasic activity of the locus coreleus, releasing noradrenaline, codes decision outcomes (to optimize performance and exploit predictable rewards), whereas fluctuations in tonic activity allows current behavior to be relinquished (to facilitate exploration) (Aston-Jones and Dayan and Yu, 2006;Yu and Dayan, 2005).…”
Section: Scope Of Reviewmentioning
confidence: 99%
“…Moreover, treatments that increase serotonin activity can have the effect of reversing these biases so that they can enhance the processing of positive emotional signals and memory for positive information (Harmer et al, 2004). Thus, disturbances in serotonin function, achieved by pharmacological challenge or through psychopathology, may influence the parameters that determine outcome values in reinforcement learning modelsFincluding longer-term rewards rates (Daw et al, 2002) or delay parameters (Doya, 2008)Fprecisely by influencing the cognitive appraisal of dilemmas giving rise to these outcomes and the appraisal of the decision outcomes themselves.…”
Section: Serotonin and The Idea Of 'Appraised' Valuesmentioning
confidence: 99%